An Assessment of Health Priorities Among a Community Sample of Somali Adults - Mohamed, Ahmed A. (J Immigr Minor Health, 2021)
Somali immigrants are one of the largest African populations to resettle in the United States since 1990. There is an emerging literature base of disease-specific studies among Somali immigrants. However, we are aware of no studies on the health priorities for Somalis from the community’s perspective. Somali adults in Minnesota completed a survey conducted by a community-based participatory research partnership on individual and community health priorities. Data were reported as counts and frequencies. 646 participants completed the survey. The most important health issues for individuals and their families were health behaviors (22.7%), diabetes (18.2%), and hypertension (14.4%), while those of the community were diabetes (22.5%), hypertension (18.8%) and weight (15.9%). This study found a significant overlap of health priorities among Somali individuals and their families compared to the community. These health priorities underscore the need to focus on non-communicable diseases among Somali immigrants.